Sustainable Development Legal Policies In The Implementation Of Sustainable Construction At Indonesia - Agustina Agustina; Triono Eddy (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
construction in Indonesia, and comprehensively discuss legal policies in overcoming the challenges and obstacles of sustainable construction. This type of research is normative juridical with a descriptive-analytical approach to discuss existing legal symptoms and problems and test them based on legislation and legal norms. The results of this research show that the legal regulation of sustainable development and construction is regulated in: the environmental protection and management law, the construction services law, the Presidential Regulation on the implementation of achieving sustainable development goals, and the PUPR ministerial regulation on guidelines for implementing sustainable construction in conjunction with the PUPR ministerial regulation on assessing the performance of green buildings. Legal policies in facing challenges and obstacles to sustainable development and construction are carried out through penal policies, namely strengthening regulations as guidelines for sustainable development and construction, the obligation to make strategic environmental studies in every government program and policy, non-penal by involving community participation in development, education, improving the quality of human resources and mastering green construction technology.